(untitled) - Pizzo, Stephen (New York, 1989)
As a gripping warning about the dangers of the deregulation of American banks, this book tells the story of the collapse of the nation's thrifts. As millions of Americans deposited life-savings, scores of executives risked the money in ventures that failed, causing the American taxpayers to suffer.
Keywords: Savings and loan associations,Hội tiết kiệm và cho vay; Corrupt practices,Thủ đoạn hối lộ; United States,Hoa Kỳ